Estrogen receptor agonists alleviate cardiac and renal oxidative injury in rats with renovascular hypertension - YEGEN, BERRAK; ŞENER, GÖKSEL; KASIMAY ÇAKIR, ÖZGÜR; ÖZDEMİR KUMRAL, ZARİFE NİGAR (TAYLOR & FRANCIS INC, 2016)
Although endogenous estrogen is known to offer cardiac and vascular protection, the involvement of estrogen receptors in mediating the protective effect of estrogen on hypertension-induced cardiovascular and renal injury is not fully explained. We aimed to investigate the effects of estrogen receptor (ER) agonists on oxidative injury, cardiovascular and renal functions of rats with renovascular hypertension (RVH). Female Sprague-Dawley rats were randomly divided as control and RVH groups, and RVH groups had either ovariectomy (OVX) or sham-OVX. Sham-OVX-RVH and OVX-RVH groups received either ER agonist diarylpropiolnitrile (1 mg/kg/day) or ER agonist propyl pyrazole triol (1 mg/kg/day) for 6 weeks starting at the third week following the surgery. At the end of the 9(th) week, systolic blood pressures were recorded, cardiac functions were determined, and the contraction/relaxation responses of aortic rings were obtained. Serum creatinine levels, tissue malondialdehyde, glutathione, superoxide dismutase, catalase levels, and myeloperoxidase activity in heart and kidney samples were analyzed, and Na+, K+-ATPase activity was measured in kidney samples. In both sham-OVX and OVX rats, both agonists reduced blood pressure and reversed the impaired contractile performance of the heart, while ER agonist improved renal functions in both the OVX and non-OVX rats. Both agonists reduced neutrophil infiltration, lipid peroxidation, and elevated antioxidant levels in the heart, but a more ER-mediated protective effect was observed in the kidney. Our data suggest that activation of ER might play a role in preserving the function of the stenotic kidney and delaying the progression of renal injury, while both receptors mediate similar cardioprotective effects.
Keywords: Cardiac injury; estrogen receptor; menopause; oxidative stress; renal injury; renovascular hypertension; CORONARY-HEART-DISEASE; ORGAN DAMAGE; BLOOD-PRESSURE; ALPHA; MECHANISMS; PROTECTS; STRESS; ACTIVATION; DEFICIENT; MENOPAUSE